Outcomes of Vitrectomy Combined with Scleral Buckling for Eyes with Early Recurrence of Simple Rhegmatogenous Retinal Detachment Previously Treated by Pars Plana Vitrectomy. (17th December 2020) - Tatsumi, Tomoaki; Baba, Takayuki; Iwase, Takehito; Nizawa, Tomohiro; Miura, Gen; Yokouchi, Hirotaka; Yamamoto, Shuichi
Abstract : Purpose . To investigate the outcomes of pars plana vitrectomy (PPV) combined with scleral buckling (SB) in treating eyes with an early recurrent rhegmatogenous retinal detachment (rRRD). Methods . This was a retrospective, interventional case series of 21 eyes with an early rRRD treated by PPV combined with SB. The significance of the associations between the variants before the surgeries and the final best-corrected visual acuity (BCVA) was determined. Results . The average age of the patients was 61.0 ± 9.6 years. A retinal reattachment was observed in 20 of 21 eyes (95.2%) after a single reoperation. The BCVA was 0.91 ± 0.90 logMAR units before the initial surgery and 0.94 ± 0.94 logMAR units before the reoperations, and it improved significantly to 0.49 ± 0.50 logMAR units after the reoperation (P = 0.016, P = 0.002, respectively). The preoperative BCVA was significantly correlated with the final BCVA (P = 0.043, r = 0.445 before the primary surgery; P < 0.001, r = 0.885 before reoperation). Conclusions . The reattachment of an early recurrent retinal detachment by PPV with SB is effective.